The innovative evolution of teaching materials: Trends and future prospects - Kunwar, Rajendra; Shrestha, Suman Kumar; Adhikari, Sapana (Journal of Research in Instructional, 2025)
The way we teach has changed a lot over time, thanks to new technology and different ideas about how to learn. This article looks at how teaching materials have changed from the past to now and what might happen in the future. It starts with old tools like clay tablets and papyrus scrolls and moves to modern digital and interactive tools. Important changes, like the printing press, audiovisual aids, and digital resources, are talked about because they made big differences in how we teach. The article also talks about current trends, like using artificial intelligence (AI), virtual reality (VR), and augmented reality (AR), and open educational resources. These trends are changing how we learn by making it more fun, personalized, and easier to access. In the future, the review expects that new technologies will keep pushing the boundaries of teaching materials, with AI, VR, AR, and blockchain being very important. The article ends with suggestions for policies to help these changes, focusing on investing in digital tools, training for teachers, and making sure everyone can benefit from these new technologies. This detailed look gives useful ideas for teachers, leaders, and researchers, showing how new teaching materials can make learning better, more fun, and more fair for everyone.